2023
DOI: 10.3390/ph16111577
|View full text |Cite
|
Sign up to set email alerts
|

Naphthoquinones as a Promising Class of Compounds for Facing the Challenge of Parkinson’s Disease

Thaís Barreto Santos,
Leonardo Gomes Cavalieri de Moraes,
Paulo Anastácio Furtado Pacheco
et al.

Abstract: Parkinson’s disease (PD) is a degenerative disease that affects approximately 6.1 million people and is primarily caused by the loss of dopaminergic neurons. Naphthoquinones have several biological activities explored in the literature, including neuroprotective effects. Therefore, this review shows an overview of naphthoquinones with neuroprotective effects, such as shikonin, plumbagin and vitamin K, that prevented oxidative stress, in addition to multiple mechanisms. Synthetic naphthoquinones with inhibitory… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 147 publications
0
3
0
Order By: Relevance
“…Additionally, they inhibit enzymes involved in the generation of ROS, including NADPH oxidase in phagocytic cells, xanthine oxidase, mitochondrial cytochrome C oxidase, and microsomal monooxygenases. These effects can be attributed to the activation of the Keap1/Nrf2/ARE signaling pathway by 1,4-naphthoquinones, which help regulate the cellular redox status [18,22]. At the same time, we showed that U-443 and U-573 partially block NO formation in RAW 264.7 cells.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Additionally, they inhibit enzymes involved in the generation of ROS, including NADPH oxidase in phagocytic cells, xanthine oxidase, mitochondrial cytochrome C oxidase, and microsomal monooxygenases. These effects can be attributed to the activation of the Keap1/Nrf2/ARE signaling pathway by 1,4-naphthoquinones, which help regulate the cellular redox status [18,22]. At the same time, we showed that U-443 and U-573 partially block NO formation in RAW 264.7 cells.…”
Section: Discussionmentioning
confidence: 69%
“…It has been established that these compounds possess a diverse range of biological activities, including antifungal, antibacterial, antioxidant, cardioprotective, hepatoprotective, anti-ischemic, and various other properties. There is an increasing number of scientific papers exploring the protective role of 1,4-naphthoquinones in disorders characterized by the degeneration of neurons such as AD and PD [10][11][12][13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Confirming that acetylation, raising the size of the substituent groups, is only a medicinal chemistry tool to enhance membrane permeation [ 60 ]. The relevance of the results pointed to a leading approach for the identification of multitargeting hybrid compounds, a strategy receiving increased scientific interest in both neurodegenerative [ 61 , 62 , 63 ] and other diseases [ 64 ], including cancer [ 65 , 66 ].…”
Section: Discussionmentioning
confidence: 99%